Preventive effects of Mycobacterium tuberculosis DNA vaccines on the mouse model with latent tuberculosis infection - Liang, Yan; Li, Xiaoping; Yang, Yourong; Xiao, Li; Liang, Yumei; Mi, Jie; Xue, Yong; Gong, Wenping; Wang, Lan; Wang, Jie; Zhang, Junxian; Shi, Yingchang; et al. (Frontiers in Immunology, 2023)
Background About a quarter of the world’s population with latent tuberculosis infection (LTBI) are the main source of active tuberculosis. Bacillus Calmette Guerin (BCG) cannot effectively control LTBI individuals from developing diseases. Latency-related antigens can induce T lymphocytes of LTBI individuals to produce higher IFN-γ levels than tuberculosis patients and normal subjects. Herein, we firstly compared the effects of M. tuberculosis (MTB) ag85ab and 7 latent DNA vaccines on clearing latent MTB and preventing its activation in the mouse LTBI model. Methods A mouse LTBI model was established, and then immunized respectively with PBS, pVAX1 vector, Vaccae vaccine, ag85ab DNA and 7 kinds of latent DNAs (including rv1733c, rv2660c, rv1813c, rv2029c, rv2628, rv2659c and rv3407) for three times. The mice with LTBI were injected with hydroprednisone to activate the latent MTB. Then, the mice were sacrificed for the bacterial count, histopathological examination, and immunological evaluation. Results Using chemotherapy made the MTB latent in the infected mice, and then using hormone treatment reactivated the latent MTB, indicating that the mouse LTBI model was successfully established. After the mouse LTBI model was immunized with the vaccines, the lung colony-forming units (CFUs) and lesion degree of mice in all vaccines group were significantly decreased than those in the PBS group and vector group (P<0.0001, P<0.05). These vaccines could induce antigen-specific cellular immune responses. The number of IFN-γ effector T cells spots secreted by spleen lymphocytes in the ag85ab DNA group was significantly increased than those in the control groups (P<0.05). In the splenocyte culture supernatant, IFN-γ and IL-2 levels in the ag85ab, rv2029c, and rv2659c DNA groups significantly increased (P<0.05), and IL-17A levels in ag85ab and rv2659c DNA groups also significantly increased (P<0.05). Compared with the PBS and vector groups, the proportion of CD4+CD25+FOXP3+ regulatory T cells in spleen lymphocytes of ag85ab, rv2660c, rv2029c, and rv3407 DNA groups were significantly reduced (P<0.05). Conclusions MTB ag85ab and 7 kinds of latent DNA vaccines showed immune preventive efficacies on a mouse model of LTBI, especially the rv2659c, and rv1733c DNA. Our findings will provide candidates for the development of new multi-stage vaccines against TB.